The economic rationale for investing in stunting reduction - Hoddinott, John F.; Alderman, Harold; Behrman, Jere R.; Haddad, Lawrence James; Horton, Susan (Wiley, 2013)
This paper outlines the economic rationale for investments that reduce stunting. We present a framework that illustrates the functional consequences of stunting in the 1000 days after conception throughout the life cycle: from childhood through to old age. We summarize the key empirical literature around each of the links in the life cycle, highlighting gaps in knowledge where they exist. We construct credible estimates of benefit–cost ratios for a plausible set of nutritional interventions to reduce stunting. There are considerable challenges in doing so that we document. We assume an uplift in income of 11% due to the prevention of one fifth of stunting and a 5% discount rate of future benefit streams. Our estimates of the country‐specific benefit‐cost ratios for investments that reduce stunting in 17 high‐burden countries range from 3.6 (DRC) to 48 (Indonesia) with a median value of 18 (Bangladesh). Mindful that these results hinge on a number of assumptions, they compare favourably with other investments for which public funds compete.